Workplace environment, leader communication and hotel employee retention : job satisfaction as a mediator - Haslina Halim; Tengku Mohd Asrulhaidar Tengku Radin; Farah Lina Azizan; Nazrul Shazleen Nazri (Penerbit Universiti Kebangsaan Malaysia, 2021)
Every organisation has invested its time, effort and resources to recruit, train and pay employees’ salaries. These investments are important to ensure that the organisation can produce high-quality employees who will remain with the organisation for a long period of time and be part of the successful members of the service team. Although a lot has been done to ensure that employees remain with the organisation, research has found that employee retention remains to be a problem to most organisations. In validating whether the findings from past studies are still consistent with the present situation, the present research aims to further investigate whether work environment, leader communication and job satisfaction still present significant relationships with hotel employee retention. In total, 550 self-administered questionnaires were distributed to hotel employees attached to 3-star and 4-star hotels located in Klang Valley, Malaysia. Of the total being distributed, 329 were returned and considered usable for data analysis. The hypothesised relationships between variables were tested using the multiple regression analysis. The findings reveal that workplace environment, leader communication and job satisfaction are significantly related to hotel employee retention. The results also demonstrate that job satisfaction mediates the relationship between workplace environment, leader communication and employee retention. The findings of this research advance the understanding of employee retention and create awareness among hotel management to better appreciate the dimensions of transformation which are essential towards ensuring employee job satisfaction. This will consequently lead to a long-term employee retention. Apart from the findings, the paper also highlights the limitations and suggestions for future research.